Ajim - A. Louis (Encyclopédie berbère, 1986)
Introduction Accurate assessment of heat strain at initial stay time (IST; core temperature 38.0°C or Δ1.0°C above resting), when heat mitigation decisions are required, is critical for managing occupational heat exposure. We evaluated the relationship and agreement between physiological (Physiological Strain Index [PSI] and adaptive PSI [aPSI]) and perceptual (Perceptual Strain Index [PeSI]) indices during simulated occupational work performed until IST. Methods Ninety-seven healthy adults completed treadmill walking to IST at either moderate-intensity (200 W·m -2 ; 24 young [12 females] and 25 older adults [13 females]) or heavy-intensity (260 W·m -2 ; 24 young [12 females] and 24 older adults [12 females]) at wet-bulb globe temperatures (WBGT) of 26°C, 29°C, or 32°C. Core and skin temperatures, heart rate, thermal sensation, and ratings of perceived exertion were measured to calculate PSI, aPSI, and PeSI. Relationships between indices were assessed using linear mixed-effects models, and agreement was evaluated using Bland-Altman analyses. Results PeSI increased with PSI and aPSI during moderate- and heavy-intensity work (all p < 0.01). These relationships were not modified by group, environmental condition, body surface area, or aerobic fitness. However, agreement between perceptual and physiological indices was limited, showing wide limits of agreement between PSI and PeSI during moderate- (-2.3 to 4.2 AU) and heavy-intensity (-3.0 to 4.0 AU) work. The agreement between PeSI and aPSI was modestly improved but remained variable. Conclusion We show that although perceptual responses increase with physiological heat strain, they do not reliably reflect physiological burden at IST, when decisions regarding the implementation of heat mitigation strategies are required.